Mixed discretization of the time-domain MFIE at low frequencies - Ulku, H. Arda; Bogaert, Ignace; Cools, Kristof; Andriulli, Francesco P.; Bagci, Hakan (IEEE, 2017)
Solution of the magnetic field integral equation, which is obtained by the classical marching-on-in-time (MOT) scheme, becomes inaccurate when the time-step is large, i.e., under low-frequency excitation. It is shown here that the inaccuracy stems from the classical MOT scheme's failure to predict the correct scaling of the current's Helmholtz components for large time-steps. A recently proposed mixed discretization strategy is used to alleviate the inaccuracy problem by restoring the correct scaling of the current's Helmholtz components under low-frequency excitation.